Novel cycloartane triterpenoids from the Nepal native plant Caragana sukiensis. Issue 22 (15th November 2015) - Mandal, Reeta; Siva, Bandi; Phani Babu, V.S.; Suresh Babu, K.; Jagadeesh, B.; Ranjit, Rosa; Shrestha, Kanti; Gewali, Mohan Bikram
Graphical abstract: Abstract: A phytochemical study on the arial part of Caragana sukiensis resulted in the isolation of three new cycloartane triterpenoids1 –3 and their structures were fully established on the basis of detailed spectroscopic (especially 2D NMR and Mass) analysis. These new compounds possessed hemiacetal fused tetrahydropyran rings at C-15/C-16, while2 and3 also containsd -xylose moiety.